Perancangan Aplikasi E-CRM Smartrealty Berbasis Web dengan Human-Centered Design untuk Pengelolaan Leads Agen Properti - Ruwayda Ruwayda; Osly Usman; Ryna Parlyna (INDO PUBLISHING, 2026)
This research aims to design a web-based Electronic Customer Relationship Management (e-CRM) prototype application to address operational inefficiencies faced by property agents in leads management, including the lack of initial qualification data, budget mismatch, manual qualification inefficiency, and the absence of an integrated pipeline system. Problems were identified through a pre-survey of six active property agents. Smart Realty was developed using the waterfall model combined with Design Thinking and Human-Centered Design (HCD) based on ISO 9241-210:2019, producing thirteen mid-fidelity wireframes and a functional prototype comprising Smart Discovery, Pipeline Kanban, Consultation, Leads Management, Property Listing, and Dashboard & Business Funnel modules. Evaluation was conducted through black-box testing and usability testing using the System Usability Scale (SUS) involving 30 active property agent respondents. All seven black-box testing scenarios were declared Pass. The average SUS score reached 90.08 (Grade A Excellent), surpassing the industry average of 68, with an average task completion rate of 97.3% and continued use intent as a reflection of behavioral intention averaging 4.70 out of 5. The research concludes that Smart Realty meets usability standards and supports property agents' behavioral intention to transition from manual leads management to a more structured and integrated digital e-CRM system.